If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + 5y + -7 = 16y + -12 + -2y Reorder the terms: 40 + -7 + 5y = 16y + -12 + -2y Combine like terms: 40 + -7 = 33 33 + 5y = 16y + -12 + -2y Reorder the terms: 33 + 5y = -12 + 16y + -2y Combine like terms: 16y + -2y = 14y 33 + 5y = -12 + 14y Solving 33 + 5y = -12 + 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. 33 + 5y + -14y = -12 + 14y + -14y Combine like terms: 5y + -14y = -9y 33 + -9y = -12 + 14y + -14y Combine like terms: 14y + -14y = 0 33 + -9y = -12 + 0 33 + -9y = -12 Add '-33' to each side of the equation. 33 + -33 + -9y = -12 + -33 Combine like terms: 33 + -33 = 0 0 + -9y = -12 + -33 -9y = -12 + -33 Combine like terms: -12 + -33 = -45 -9y = -45 Divide each side by '-9'. y = 5 Simplifying y = 5
| x*6+115=x*15-11 | | 52=x+27 | | x+23+3x=-20-3x-27 | | 92-4x=14x+22 | | 9x^2=21x | | 2x+20=4x+6 | | x(3x-2)(x+6)= | | (3s-2)(4s+4)= | | 7x+32=x^2+4 | | 3.42/34.2 | | 3.42/24.2 | | 12=x/11 | | 8c*3v= | | -36x^2+96x-36=0 | | 2(5x+3)=4x-10 | | 1/6=6x | | 20x=460 | | 6=-3/5(4)+b | | 6=-3/5(4) | | -2x-6y=-74 | | 8x+3=6x+33 | | x+x+8+2x=240 | | 6x-(4x+3)=7 | | 6.3x=18.9 | | 9t^3+15t^2+t-6=t^2+t-6-3t^3 | | -12x^3+48x^2-36x=0 | | 8x+47=8(x+4) | | 7(4x-9)=40 | | 3x+6=-5-1x | | 3x^3+4x^4-6x^5-9x^6+14x^7-6x^8+x^9=0 | | ((a^4)/(2a^2-4a^4))*((8a^3+1)/(2a+4a^2)) | | 7(3x-9)=34 |